The Impact of Khamar Transactions on Traders and Minors - Muhammad Rizqi Hidayah; Adika Pranata; Muhammad Rizki Simamora; Alfin Tambak; Mohd. Mozaed Al Farid Sitorus; Alfiansyah Borotan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This article examines various aspects related to khamar, including its linguistic meaning, definitions, impacts, and the Islamic legal perspective on it. In Arabic, khamar means something that conceals or covers, referring to intoxicating beverages that impair rational thinking. Scholars provide various definitions of khamar, encompassing intoxicants derived from fermented grapes and other substances. From an Islamic perspective, khamar is considered to have more harmful effects than benefits, affecting social, economic, and health aspects. Although the trade of khamar may provide worldly profits, it is deemed contrary to Islamic teachings due to its potential to promote immorality and corrupt morals. The impact of khamar consumption on minors is particularly damaging, affecting their physical and mental health as well as causing broader social repercussions. Islamic legal sanctions against the consumption of khamar emphasize strict prohibition to prevent its use, although specific worldly punishments are not elaborated upon. This study highlights that despite the financial advantages it might offer, the negative consequences of khamar far outweigh its benefits and should therefore be avoided for the well-being of society.